High quality epitaxial fluorine-doped SnO2 films by ultrasonic spray pyrolysis: Structural and physical property investigation. (15th October 2017) - Zhang, Shan-Ting; Rouvière, Jean-Luc; Consonni, Vincent; Roussel, Hervé; Rapenne, Laetitia; Pernot, Etienne; Muñoz-Rojas, David; Klein, Andreas; Bellet, Daniel
Abstract: Despite its wide use in the display and photovoltaic industries, fluorine-doped tin oxide (F:SnO2, FTO) has been studied only in its polycrystalline form. In this work, we report on the first growth of epitaxial FTO thin film by ultrasonic spray pyrolysis – a simple chemical deposition method – and we reveal the structure-property interplay by investigating in details its growth, morphology and strain/defects. Epitaxial FTO films are successfully grown on (110) rutile TiO2 single crystals and form mosaic domains with an out-of-plane distribution smaller than 0.5°, showing high structural quality comparable to epitaxial films prepared by molecular beam epitaxy and pulsed-laser deposition. Owing to the large lattice mismatch with rutile TiO2, the FTO film develops significant structural defects to release the epitaxial strain and is consequently nearly fully relaxed with a slight residual strain of 0.1–0.2%. With the help of an innovative nano-beam precession electron diffraction technique, the strain distribution is mapped at the TiO2 /FTO interface, from which we identify the interfacial and secondary strain relaxation taking place mainly in the first 22 nm in the FTO film. The Hall-mobility of the epitaxial FTO films is close to the state-of-the-art and expected to improve further at lower doping concentrations. Graphical abstract: Highlights: Epitaxial F-doped SnO2 (FTO) films are deposited on (110) rutile TiO2 for the first time using ultrasonic spray pyrolysis. Epitaxial FTO film is of high structural quality with mosaic domains showing a narrow distribution of less than 0.5°. Strain map at TiO2/FTO interface reveals the first 22 nm in FTO responsible for interfacial and secondary strain relaxation.